2009
DOI: 10.4049/jimmunol.0803811
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 Tunes TCR Binding and Signal Transduction to Regulate CD8 Burst Size

Abstract: T cell burst size is regulated by the duration of TCR engagement and balanced control of Ag-induced activation, expansion, and apoptosis. We found that galectin-1-deficient CD8 T cells undergo greater cell division in response to TCR stimulation, with fewer dividing cells undergoing apoptosis. TCR-induced ERK signaling was sustained in activated galectin-1-deficient CD8 T cells and antagonized by recombinant galectin-1, indicating galectin-1 modulates TCR feed-forward/feedback loops involved in signal discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 84 publications
2
28
0
6
Order By: Relevance
“…Specific CD45 isoforms contribute to the intensity of TCR signals (55,59). Additionally, galectin-1 regulates the threshold of TCR signaling and tunes thymocyte selection (4,60). Together, these findings demonstrate that the presentation of specific N-and O-glycans by CD45 on thymocytes, influenced both by CD45 isoform usage and regulated glycosyltransferase expression, is critical for proper thymocyte development and selection involving galectin-1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific CD45 isoforms contribute to the intensity of TCR signals (55,59). Additionally, galectin-1 regulates the threshold of TCR signaling and tunes thymocyte selection (4,60). Together, these findings demonstrate that the presentation of specific N-and O-glycans by CD45 on thymocytes, influenced both by CD45 isoform usage and regulated glycosyltransferase expression, is critical for proper thymocyte development and selection involving galectin-1.…”
Section: Discussionmentioning
confidence: 99%
“…Both positive and negative thymocyte selection are regulated by galectin-1, an endogenous lectin expressed by thymic epithelial cells (2,3). Galectin-1 binding to developing thymocytes can influence the strength of T cell receptor (TCR) 2 signaling, an important factor in determining if a T cell can properly recognize antigen (3,4). Galectin-1 can also directly induce apoptosis of specific thymocyte subsets, as well as activated peripheral T cells (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, lowGal-1 but not highGal-1 is dependent on the presence of p56lck and ZAP70 and activates caspase cascade [34]. It is also reported that CD7 delivers a pro-apoptotic signal during galectin-1-induced T cell death, specifically modulates TCR signals, and inhibit IL-2 production and proliferation [38][39][40]. The presence of low concentration (20 ng/ml) of gal-1 had different consequence to the cells at various maturation stages [41].…”
Section: Discussionmentioning
confidence: 94%
“…Впер-вые название галектины было введено в 1994 году. В данное семейство белков объединены β-галактозид-связывающие лектины с консер-вативной гомологичной аминокислотной по-следовательностью углевод-распознающего до-мена (CRD, carbohydrate-recognition domain) и обладающие высоким сродством к поли-N-ацетиллактозамин-богатым гликоконъюга-там [30].…”
Section: якушина вд и дрunclassified